A framework for implementing web recommendation agent - Medeiros, Danielle; Kulesza, Uirá; Campos, André Mauricio (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
This paper presents the conception, design and implementation of an object-oriented framework for the development of recommendation user agents for Web-based applications. The framework agents can be plugged or unplugged in a non-invasive way from existing Web applications using aspect-oriented programming techniques. The framework was assessed through its instantiation to three different Web-based systems.